Internship at saber pro at the University of Cordoba (2020)
This internship was carried out at University of Córdoba in the program of Saber Pro. The purpose of this internship is to strengthen students' abilities to answer questions related to communicative competence in English from the Saber Pro test. Furthermore, the internship helped me to get experience of teaching English with university students and improve my English skills. During this experience teaching people of my age or older, I realized the importance of choosing an accurate methodology. I worked with last semester students from Different careers at University of Córdoba, I was assigned 3 groups per month from different careers, they were around 20 to 45 students per group. Besides, I took it as an opportunity to motivate non-English learners to learn English and show them how important it is to know another language. In this way, making use of new strategies and using technology, they could see English as something interesting and not as they have always considered it a compulsory and boring subject.